Analisis mutu bubuk kopi arabika gayo yang dijual di toko oleh-oleh khas Kabupaten Bener Meriah Provinsi Aceh - Zarwinda, Irma; Elfariyanti, Elfariyanti; Zakaria, Nurmalia; Humaira, Humaira (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Gayo Arabica coffee is a typical coffee produced from plantations in the Gayo area of Aceh Province, especially Bener Meriah Regency. This research aims to determine the quality of packaged coffee powder that does not have a distribution permit, which is sold in souvenir shops in Bener Meriah Regency, Aceh Province. The method used in this research is quantitative analytical descriptive. The sample used in this research was coffee powder that did not have a distribution permit, which was taken as a total sampling in 5 souvenir shops in 4 sub-districts in Bener Meriah Regency. The results of organoleptic observations on coffee powder with codes P1, P2, P3, and P4 were in the form of coarse powder, while P5 was in the form of fine powder. P1 and P2 coffee grounds are dark brown, and P3, P4, and P5 are brown. The taste of coffee powder P1, P2, P3, and P5 has no taste, and P4 tastes bitter. The overall aroma of the sample is typically aromatic. The water content test results were 0.74%, 0.66%, 0.58%, 0.14%, and 1.40%, respectively. The ash content test results were obtained: 4.60%, 4.47%, 4.37%, 44.65%, and 4.50%, respectively. The coffee essence levels were 23.97%, 25.80%, 25.70%, 25.10%, and 30.2%, respectively. The results of the quality analysis of Gayo Arabica coffee powder in the souvenir shop of Bener Meriah Regency, province, have met the quality requirements by SNI 01-3542-2004.